IMPLEMENTATION OF THE E-CATALOG SYSTEM POLICY IN LOCAL ECONOMIC EMPOWERMENT THROUGH GOODS/SERVICES PROCUREMENT IN MEDAN CITY - Farida Hanum; Nina Siti Salmaniah Siregar; Beby Masitho Batubara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Local economic empowerment through government procurement of goods and services is an important strategy to support the growth of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the implementation of the MSME e-catalog system policy in local economic empowerment in Medan City, particularly in the food and beverage sector, as well as to identify the supporting and inhibiting factors in its implementation. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and documentation. The informants consisted of MSME actors, officials from the Electronic Procurement Service (LPSE), and personnel from the Goods and Services Procurement Division of the Medan City Government. Data analysis was conducted using an interactive model comprising data reduction, data display, and conclusion drawing. The findings indicate that the MSME e-catalog system has expanded market access and increased opportunities for local MSMEs to participate in government procurement. Supporting factors include pro-MSME government policies, the availability of a local e-catalog platform, and the commitment of some procurement officials. Meanwhile, inhibiting factors include limited policy socialization, low MSME human resource capacity, insufficient technical assistance, and the lack of optimal commitment from all regional work units to prioritize local MSME products. Based on Edward III’s policy implementation theory, communication, resources, implementers’ disposition, and bureaucratic structure are key determinants of policy effectiveness. Therefore, strengthening coordination, enhancing MSME capacity, and simplifying procedures are necessary to optimize the role of the e-catalog system as an instrument for local economic empowerment in Medan City.